The effect of compound exercises (plyometrics - agility) in improving short-term anaerobic ability and speed-distinguishing strength of the muscles of the legs in the triple jump for female students in the field and field lesson (Journal of the College of Basic Education, 2022)
The importance of the research lies in presenting a study on the field and field lesson, one of the students’ lessons in the second academic year in the departments and colleges of physical education and sports sciences in Iraq. So the reason for choosing the topic was, as for the research problem, it appears in the lack of time to perform the effectiveness of the triple jump, so it is necessary to use exercises with new methods to improve the capabilities of functional and physical performance, and these methods include the method of exercises (plyometrics - agility) It is a complex method that combines during performance the application of plyometric and agility movements to improve the anaerobic ability and speed-characterized strength of the muscles of the legs when performing in the triple jump activity for the purpose of improving achievement as well. The objectives of the research were (identifying the level of anaerobic ability and speed characteristic of the muscles of the legs of the research sample and achievement in the triple jump, as well as preparing suggested compound exercises (plyometric - agility) to improve the anaerobic capacity and strength characteristic of speed and achievement in the triple jump for the research sample). The most prominent hypotheses are (there are statistically significant differences between the two dimensional tests of the experimental and control groups in the anaerobic capacity and strength characterized by speed and achievement in the triple jump for the research sample) . The research community represented the students of the second academic year in the Department of Physical Education and Sports Sciences in the College of Education for Girls, University of Kufa for the academic year 2020-2021, and their number is 45 students. They are physical tests and arithmetic and statistical equations. The spss statistical bag has been used in statistical treatments.Among the most important conclusions (the compound exercises using the method (plyometric - agility) and used by the experimental group have a positive effect on improving performance by testing the short-term anaerobic capacity of the muscles of the legs, as well as the strength characteristic of speed and achievement in the triple jump). Agility) in improving the short anaerobic ability as well as the speed characteristic of the muscles of the legs and the achievement of the triple jump for female students)